Corporate Financial Characteristics and Effective Tax Rates: Evidence from Food and Beverage Firms in Indonesia - marhamah marhamah; Ariyani Indriastuti (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
Tax is a crucial source of government revenue, yet it is often perceived as a burden by firms as it reduces net income. This divergence of interests encourages companies to engage in tax planning practices, which can be observed through the effective tax rate (ETR). This study aims to examine the role of corporate financial characteristics, namely profitability, leverage, and fixed asset intensity, in determining effective tax rates. Employing a quantitative approach, this study uses secondary data from financial statements of food and beverage companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The sample was selected using purposive sampling and analyzed using multiple linear regression. The results reveal that profitability and leverage have a positive effect on effective tax rates, while fixed asset intensity has a negative effect. These findings suggest that corporate financial characteristics play a significant role in corporate tax management. This study contributes to the tax literature and provides practical implications for corporate management and policymakers in formulating effective tax strategies.